Sebastião Uchoa Leite: poética, vozes e espaços - Dassie, Franklin Alves (2012)
This work intends to do a critical- interpretative reading of Sebastião Uchoa Leite s poetic work especially based on the book Antilogia with the aim of investiganting the image of the double matter and the forms it assumes on the metapoetics reflections, on the representation of lyric subjectivity, as well as on the configuration of spaces. Articulanting, therefore, theoretical discussions about the relations between poetry and the construction of images that responds to the points demanded by Sebastião s poetic work, we intented to demonstrate how important this articulation can be for an interpretation that questions, parting from this point, the ideas of exactitude, sureness and condensation